2018
DOI: 10.1021/acs.inorgchem.8b01284
|View full text |Cite
|
Sign up to set email alerts
|

Retention of a Paramagnetic Ground State at Low Temperatures in a Family of Structurally Related UIV Phosphates

Abstract: A new uranium fluoride phosphate, UFPO, was synthesized via a mild hydrothermal route and characterized optically, thermally, and magnetically. Two thermal transformation products, UO(PO) and UUO(PO), were discovered to be structurally related, and were subsequently synthesized for bulk property measurements. All three materials failed to follow Curie-Weiss behavior at low temperatures, attributed to the nearly ubiquitous singlet ground state of U(IV), transitioning into a Curie-Weiss paramagnetic regime at hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
2
6
0
Order By: Relevance
“…From the Curie constant, an effective magnetic moment of μ eff = 3.42 μ b per U 4+ ion at 300 K is obtained and it is slightly lower than 3.58 μ b calculated from Russell–Saunders coupling of a 3 H 4 ground state. This is normally for U( iv ) oxides 39,40 and the value falls into the range of previously reported effective magnetic moment for other mononuclear and polynuclear U( iv ) complexes (2.5–3.55 μ b ) 41,42 .…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…From the Curie constant, an effective magnetic moment of μ eff = 3.42 μ b per U 4+ ion at 300 K is obtained and it is slightly lower than 3.58 μ b calculated from Russell–Saunders coupling of a 3 H 4 ground state. This is normally for U( iv ) oxides 39,40 and the value falls into the range of previously reported effective magnetic moment for other mononuclear and polynuclear U( iv ) complexes (2.5–3.55 μ b ) 41,42 .…”
Section: Resultssupporting
confidence: 77%
“…From the Curie constant, an effective magnetic moment of m eff ¼ 3.42 m b per U 4+ ion at 300 K is obtained and it is slightly lower than 3.58 m b calculated from Russell-Saunders coupling of a 3 H 4 ground state. This is normally for U(IV) oxides 39,40 and the value falls into the range of previously reported effective magnetic moment for other mononuclear and polynuclear U(IV) complexes (2.5-3.55 m b ) 41,42 . Below 150 K, the magnetic susceptibility curve deviates from Curie-Weiss law and it is mainly due to the formation of f 2 electronic singlet of U(IV) at low temperature and the population eliminating process of thermally excited state.…”
Section: Magnetic Propertiessupporting
confidence: 81%
“…In uranium fluoride systems it has been shown that the singlet ground state is essentially always observed. ,, Similarly, in normal oxide systems, while the temperature dependence of the triplet to singlet state transition is shifted, one often still observes a single ground state at low temperatures. In uranium phosphates, on the other hand, a different picture has emerged and examples of compositions such as UFPO 4 have been reported in which the triplet state is preserved to the lowest temperatures measured.…”
Section: Introductionmentioning
confidence: 99%
“…The synthetic challenges can be overcome by using the mild hydrothermal synthesis route. The most significant challenge present, however, is intrinsic to U­(IV), specifically the fact that U­(IV) tends to undergo a transition from a magnetic triplet to a nonmagnetic singlet ground state by pairing of the two 5 f electrons . It has been demonstrated, however, that the crystal electric field effects in some fluoride compounds do not lead to this transition, although the resulting phases, so far, are limited to those that exhibit only paramagnetic behavior. , In fact, there are only a few binary and ternary U­(IV) compounds that have been shown to undergo ferro- or antiferromagnetic transitions, while there is no ferrimagnetic U­(IV) compounds reported so far. …”
mentioning
confidence: 99%
“…28 It has been demonstrated, however, that the crystal electric field effects in some fluoride compounds do not lead to this transition, although the resulting phases, so far, are limited to those that exhibit only paramagnetic behavior. 29,30 In fact, there are only a few binary and ternary U(IV) compounds that have been shown to undergo ferro-or antiferromagnetic transitions, while there is no ferrimagnetic U(IV) compounds reported so far. 31−34 In order to overcome the singlet ground state transition and to develop an approach to the synthesis of U(IV) magnetic materials, we sought to induce a persistent magnetic ordering on the U(IV) cations by introducing other magnetic ions, such as lanthanides and transition metals (Scheme 1).…”
mentioning
confidence: 99%